2022
DOI: 10.55275/jposna-2022-0075
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique to Remove Plaster Ponseti Clubfoot Casts

Abstract: Serial Ponseti-style plaster of Paris casts are considered the gold standard treatment for clubfoot in infants. In conjunction with cast application, weekly cast removals are a necessary part of treatment, predisposing this patient population to cast saw injuries. Extensive research and education have been devoted to eliminating iatrogenic cast saw injuries. However, decreasing experience and familiarity with cast saws lead to a 1-2% incidence rate of cast saw burns or abrasions. While alternatives such as soa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Further, they are more reliant on partial/general sedation and are more likely to perform tenotomies in the OR. A large percentage of respondents have observed cast saw injuries, indicating a need for the profession to develop and utilize safer methods for cast removal [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, they are more reliant on partial/general sedation and are more likely to perform tenotomies in the OR. A large percentage of respondents have observed cast saw injuries, indicating a need for the profession to develop and utilize safer methods for cast removal [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monárrez et al suggested that dividing the Ponseti cast used for clubfoot management on only 1 side rather than the standard bivalve approach will reduce the incidence of cast-saw injuries during cast removal 72 . In a prospective randomized study, Li et al concluded that the routine use of tourniquets during high tibial osteotomies did not lead to a reduction in surgery duration, the incidence of intraoperative complications, or postoperative blood loss 73 .…”
Section: Practical Tips and Pearlsmentioning
confidence: 99%